Investigation of the effects of b-fit exercise protocol applications on anthropometric parameters of young women - Rafet Unver (Ozlem Book Center, 2023)
B-fit gyms were established in 2006 to offer women who do not have much knowledge and experience in physical activity and exercise the opportunity to exercise correctly and effectively. The B-fit exercise protocol applied in these halls consists of resistance and aerobic exercises aimed at working all muscle groups of the body. When the studies examining the B-fit exercise protocol in the literature are examined, it is not stated that the ages of the research participants have a wide range and how many participants are at what age. Therefore, this study is important in terms of clearly revealing the effects of the B-fit exercise protocol on the anthropometric characteristics of young female participants (18-20 years old). Twenty-two female participants between the ages of 18-20 who do sports at least 5 days a week in B-fit Sports Centers and do not follow any diet program participated voluntarily in this descriptive, cross-sectional study. At the beginning of the study, the mean body weight of the participants was 76.50±18.80, and the mean height was 165.13±4.44. Participants participated in the B-fit exercise protocol five days a week for eight weeks. During the study, the participants were asked to continue their daily routines and not make any changes in their eating habits. When the research findings were examined, it was observed that there was a statistically significant difference between the pretest-posttest averages of the participants' body weights, waist, chest, hip, abdomen, leg, arm and thigh circumferences (p<0.05).